The relationship between safety management practices and safety compliance: A study among assistant medical officer in a government hospital in northern peninsular Malaysia - Baskaran, Rajaram (2020)
The present study investigated the relationship between safety management practices and safety compliance of assistant medical officer (AMO) in a government hospital in northern peninsular Malaysia . The safety management practices are management commitment, safety training, safety communication and feedback, employees involvement, safety rules and procedures and safety promotion policies. The questionnaire is consisted of 42 items adapted from the previous studies. The questionnaire was distributed to 120 AMO in a government hospital in northern peninsular Malaysia for data collection and 100 data were analyzed using SPSS version 26.0. The findings showed that management commitment, workers involvement and safety training positively and significantly affected safety compliance where as safety communication and feedback, safety rules and procedures and safety promotion policies negatively significantly influencing safety compliance. Finally, managerial and theoretical implications are discussed and recommendations for future researchers.